Viral mimicry evasion: a new role for oncogenic KRAS mutations - Raymond Chen; Aobo He; Daniel D. De Carvalho (Molecular Oncology)
“Viral mimicry” refers to the induction of an innate immune response and interferon signaling by endogenous stimuli such as double‐stranded RNA (dsRNA). This response has been shown to have strong cancer therapeutic potential, including by enhancing the effectiveness of immune checkpoint inhibition (ICI) therapies, and may represent a tumor suppression mechanism that needs to be overcome for malignant transformation to proceed. In a recent study, Zhou and colleagues identify KRAS, a frequently mutated oncogene, as a negative regulator of dsRNA and viral mimicry in an ICI‐resistant colorectal cancer model. Oncogenic KRASG12D mutations downregulate the RNA‐binding protein DDX60 by activating the AKT signaling pathway, which inhibits STAT3, a critical transcription factor regulating DDX60 and other interferon‐stimulated genes. Overexpression of DDX60, which competitively binds to dsRNA to prevent RISC‐mediated degradation, or targeting of KRASG12D elevated dsRNA levels, resulting in viral mimicry activation and potentiation of ICI treatment. These results establish KRAS as a promising target to sensitize immune “cold” tumors to ICI therapy and demonstrate the potential role of oncogenic mutations in viral mimicry evasion during tumorigenesis.